Soccer stadiums as tools of economic development - Kacirek, Ryan (Kansas State University, 2015)
Few things dominate American culture like sport. Sports function as a universal language, as something that people identify with. The provision of stadiums in the United States represents some of the largest public investments found on a municipal level. Over the past 10 years soccer has become one of the most popular sports in the U.S. Consequently, the provision of soccer stadiums is becoming an important economic issue. The lack of research regarding the economic impact of soccer stadiums and the techniques in which city planners can address the economic performance of soccer stadiums will be addressed in this study. The study employs a multiple regression analysis to understand the relationship between economically successful sports stadium characteristics and the economic impact of soccer stadiums. The multiple regression analysis considers each of the 16 Major League Soccer stadiums in the U.S. and discovers the relationship between the economic impacts of each stadium and the presence of successful sports stadium characteristics at those stadiums. The regression analysis resulted in a conditional estimate of the impact of successful sports stadium characteristics on the economic impact of soccer stadiums. No significance can be drawn between the economic impact of soccer stadiums and successful sports stadium characteristics. Although successful sports stadium characteristics have little impact on economic performance, planners should still encourage the use of successful characteristics in stadiums. Planners have the skill set to plan for stadiums that benefit the public economically, socially, psychologically, and environmentally. Planners must continue to find ways to ensure that soccer stadiums have a positive impact on the cities that build them.
Keywords: Economic Development; Soccer Stadium; Soccer Stadium Economic Impact; Sport Stadium Economic Impact; Urban Planning; Urban Planning (0999)